Bilateral Vertebral Artery Dissection after a Chiropractic Therapy Session - Romero, Flavio Ramalho [UNESP]; Vieira, Rodolfo Brum [UNESP]; Macedo de Freitas, Carlos Clayton [UNESP] (Georg Thieme Verlag Kg, 2017)
Vertebral artery dissection (VAD) is a rare and sometimes unrecognized cause of stroke in patients younger than 45 years. Herein, we describe a very rare case of bilateral vertebral artery dissection after a session of cervical therapy manipulation (chiropractic).
Keywords: vertebral artery dissection; cervical manipulation; stroke